Factors associated with the use of curative healthcare services in Bunia Health Zone facilities, Ituri Province, Democratic Republic of the Congo - Kpane, C. F.; Bisingurege, K. F.; Zawadi, M.; Baba, Amuda; Chelo, N. H.; Tsongo, K. Z.; Wembonyama, O. S. (Orapuh Journal, 2025)
IntroductionAccess to quality curative care remains a challenge in many low-resource settings. The World Health Organization (WHO) identifies healthcare utilization as a key determinant of public health outcomes.PurposeThis study aimed to identify household and organizational factors associated with the use of curative healthcare services in the Bunia Health Zone, Democratic Republic of Congo (DRC).MethodsA cross-sectional study was conducted in January–February 2023 using a multi-stage cluster sampling technique. Data from 824 households were collected via structured questionnaires. Logistic regression analyses were performed to identify factors associated with facility choice.ResultsAmong households reporting illness in the last 30 days, 68.7% used non-subsidized private facilities. Significant factors influencing this choice included satisfaction with care (OR = 5.50, p = 0.001), good reception (OR = 5.41, p = 0.012), availability of medicine (OR = 3.26, p = 0.006), affordable cost (OR = 4.89, p = 0.010), and smaller household size (OR = 3.52, p = 0.008).ConclusionTo enhance the utilization of subsidized services, health system interventions should prioritise improving patient satisfaction, affordability, waiting times, and drug availability.